2014
DOI: 10.1186/1745-6215-15-231
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a behavioral activation intervention among depressed US Latinos with limited English language proficiency: study protocol for a randomized controlled trial

Abstract: BackgroundMajor depressive disorder is highly prevalent among Latinos with limited English language proficiency in the United States. Although major depressive disorder is highly treatable, barriers to depression treatment have historically prevented Latinos with limited English language proficiency from accessing effective interventions. The project seeks to evaluate the efficacy of behavioral activation treatment for depression, an empirically supported treatment for depression, as an intervention that may a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 65 publications
(80 reference statements)
2
11
0
Order By: Relevance
“…Briefly, ¡Aptívate! is a self-help Spanish language adaptation of Brief BA (Collado et al, 2014b;Lejuez et al, 2011). Within ¡Aptívate!, the user identifies individualized values and associated activities across five life areas, including relationships, daily responsibilities, recreation, career and education, and health.…”
Section: Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, ¡Aptívate! is a self-help Spanish language adaptation of Brief BA (Collado et al, 2014b;Lejuez et al, 2011). Within ¡Aptívate!, the user identifies individualized values and associated activities across five life areas, including relationships, daily responsibilities, recreation, career and education, and health.…”
Section: Interventionsmentioning
confidence: 99%
“…Because U.S. Latinx are a highly heterogeneous group with varied sociocultural and historical origins (González Burchard et al, 2005), an appropriate depression psychotherapy to adapt for mobile app delivery must be idiographic to accommodate personal beliefs/ values on a case-by-case basis. Brief Behavioral Activation Treatment for Depression (Brief BA;Collado et al, 2014b;Lejuez et al, 2011) is an idiographic, straightforward, concise, yet evidence-based psychotherapy for depression. Collado et al (2014a;2014b) developed a direct Spanish language translation of Brief BA, delivered in person using paper forms, for Latinx adults with LEP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its Spanish version showed adequate psychometric properties [ 34 ]. In a recent study conducted with Latino participants with depression, a BA intervention was found to produce not only a greater decrease in depressive symptoms than supporting counseling, but also increased activation and environmental reward [ 35 ]. The Cronbach alpha for the Activation subscale is .81.…”
Section: Data Collectionmentioning
confidence: 99%
“…Moreover, BATD has been used efficaciously with depressed individuals with a range of other comorbidities including substance use (Daughters et al, 2008; MacPherson et al, 2010; Magidson et al, 2011), anxiety/trauma (Gros et al, 2012; Strachan, Gros, Ruggiero, Lejuez, & Acierno, 2012), and physical health conditions such as cancer (Hopko et al, 2011). BATD has been tested in a variety of patient populations including college students (Gawrysiak et al, 2009; Reynolds et al, 2011), veterans (Egede et al, 2015), Spanish-speaking Latinos (Collado, Calderon, MacPherson, & Lejuez, 2016; Collado, Castillo, Maero, Lejuez, & MacPherson, 2014; Collado, Long, MacPherson, & Lejuez, 2014), and survivors of systematic violence in Kurdistan, Iraq (Bolton et al, 2014). A key strength of BATD, which contributes to its popularity, is that it is simple, straightforward, and as such is easy for clinicians to be trained in and to use with their patients (e.g., Bolton et al, 2014).…”
mentioning
confidence: 99%